Development of a detailed bathymetry map of the Nhat Le estuary, Quang Binh province by remote sensing image treatment - Huong, Le Thi; Van, Le Thi Hong; Lien, Nguyen Thi Viet; Thuy, Trinh Thi Thu; Nga, Le Nhu; Ha, Dang Song (Vietnam Journal of Mechanics, 2024)
Multispectral remote sensing images with the advantages of low cost, wide area coverage, and increased resolution have been widely used recently for determining the bathymetry of coastal waters. In this study, the correlation equation is developed based on the Landsat 8 OLI satellite images captured on September 22, 2022, and the survey data measured during the time period of September 12–22, 2022, was used for mapping bathymetry in the Nhat Le Estuary area, Quang Binh Province, a relatively clear area from sediment. The correlation between the image and the field survey data is quite good, with R2 = 0.88. This shows that Landsat 8 OLI data is suitable for mapping sea areas with depths up to 20 m.